2002
DOI: 10.1074/jbc.m203602200
|View full text |Cite
|
Sign up to set email alerts
|

CacyBP/SIP, a Calcyclin and Siah-1-interacting Protein, Binds EF-hand Proteins of the S100 Family

Abstract: Recently, a human ortholog of mouse calcyclin (S100A6)-binding protein (CacyBP) called SIP (Siah-1-interacting protein) was shown to be a component of a novel ubiquitinylation pathway regulating ␤-catenin degradation (Matsuzawa, S., and Reed, J. C. (2001) Mol. Cell 7, 915-926). In murine brain, CacyBP/SIP is expressed at a high level, but S100A6 is expressed at a very low level. Consequently we carried out experiments to determine if CacyBP/SIP binds to other S100 proteins in this tissue. Using CacyBP/SIP affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 34 publications
1
107
0
1
Order By: Relevance
“…Nuclear translocation of SIP is regulated by different motifs As reported (Filipek et al, 2002a;Santelli et al, 2005), the N-terminal amino acids (aa) 1-47 of SIP comprise a self-dimerization domain, and the C-terminal contains binding motifs for SKP1 and S100 proteins (Figure 4a). To explore the mechanisms underlying nuclear translocation of SIP, the protein sequence of SIP was analyzed computationally.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Nuclear translocation of SIP is regulated by different motifs As reported (Filipek et al, 2002a;Santelli et al, 2005), the N-terminal amino acids (aa) 1-47 of SIP comprise a self-dimerization domain, and the C-terminal contains binding motifs for SKP1 and S100 proteins (Figure 4a). To explore the mechanisms underlying nuclear translocation of SIP, the protein sequence of SIP was analyzed computationally.…”
Section: Resultsmentioning
confidence: 81%
“…It has been shown that S100 family members interact with the C-terminal region of SIP (Filipek et al, 2002a;Bhattacharya et al, 2005) and some of the members, such as S100A1, S100A2, S100A6 and S100B, are involved in apoptosis regulation, and many S100 proteins display cellular translocation in response to various stimuli (Hsieh et al, 2002;Orre et al, 2007;Joo et al, 2008). Besides, SIP has been found to interact with ERK1/2 and downregulate ERK activity (Kilanczyk et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, other members of S100A7 proteins such as S100A1, S100A6, S100A12, S100A7 inhibits SCCOC progression G Zhou et al S100B and S100P, were shown to interact with SIP in a calcium-dependent manner (Filipek et al, 2002). It remains to be determined whether S100A7 can also interact with SIP and participate in Siah-SIP-mediated b-catenin degradation as previously reported (Liu et al, 2001;Matsuzawa and Reed, 2001;Fukushima et al, 2006).…”
Section: Discussionmentioning
confidence: 81%
“…Calcyclin-binding protein (CacyBP), a 30 kDa protein, was identified on the basis of its ability to interact with S100 proteins, including S100A6, S100A1, S100A12, S100B, and S100P, in a calcium-dependent manner (1)(2)(3). CacyBP/SIP is highly expressed in the mouse and in rat brain, liver, spleen, and stomach, and weakly in rat lung and kidney (4).…”
Section: Introductionmentioning
confidence: 99%